PENERAPAN SANKSI PELANGGARAN KODE ETIKPROFESI NOTARIS OLEH DEWAN KEHORMATAN IKATAN NOTARISINDONESIA DI KOTA TANGERANG SELATAN - ANGRAINI, RIA TRI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The study aims to identify and analyze, how the forms of code violations committed by a notary in South Tangerang City and to analyze the Honor Council sanctions imposed Indonesian Notaries Association as a professional organization can bind to the notary who violates the code of conduct in South Tangerang City. The data gathered from both literature research and field research using empirical approach to the problem legally and analyzed using qualitative methods of the research method that produces descriptive qualitative data. Primary data and secondary data collected by interviewing, and researchers to study the document library. Based on research conducted by the author which is the subject of research is that respondents who have a close connection with the problem under study and the informant, the person who becomes a source of data / information research. The results showed that Notary's violation happens many times. This is due to the intense competition in the notary's work which originated from the growing number of notaries. This condition will get worse and become a dilemma because of the weakness of the socialization of the code of conduct and supervision of professional organizations conducted by the notary in this case Indonesian Notaries Association. For the Honor Council in coordination with the Council of Trustees is authorized to conduct examinations for such violations and may impose strict sanctions to notaries who violate the code of ethics.